ผลกระทบจากความยาวคลื่นแสงที่แตกต่างกันต่อพฤติกรรมการตอบสนองและศึกษาโครงสร้างชั้นเซลล์รับภาพของปลากะพงขาว Lates calcarifer (Bloch, 1790) ระยะวัยรุ่น - ศดานันท์ แก้วปราณี (จุฬาลงกรณ์มหาวิทยาลัย, 2018)
Fish biology and behavior are influenced by light. Extended exposed to the certain wavelength under which teleost larvae and juvenile are reared affects growth and survival in complex ecosystem. The nature and extent of the effect of this exposure varies among species. Our study aims to determine the effect of exposing to four different wavelength light [red (710nm), blue (453 nm) and green (510nm)] on growth, behavioral response, visibility and the structure of the retinal layer in the juvenile seabass. We observed three behavioral categories (feeding, schooling and swimming) and measure the structure of the retinal layer. The juvenile sea bass were raised for 4 weeks for the experiment. The juvenile seabass reared under the fluorescent red light wavelength (710nm) had scored best in the behavioral observation, least time to eat artemia and had the thickest retina layers when compared to the other three wavelength.